Strickberger's evolution - Hall, Brian K.; Hall, Brian K.; Hallgrimsson, Benedikt (Burlington, Jones & Bartlett, 2014)
Now with a new full color design and art program, the Fifth Edition of Strickberger's Evolution is updated with the latest data and updates from the field. The authors took care to carefully modify the chapter order in an effort to provide a more clear and student-friendly presentation of course material. The original scope and theme of this popular text remains, as it continues to present an overview of prevailing evidence and theories about evolution by discussing how the world and its organisms arose and changed over time. New boxed features concentrating on modern and exciting research in the field are included throughout the text. Preview content today! Download chapters 1 and 3 from the Sample Materials tab. A dynamic new art program and enhanced design adds clarity to the text A more student-friendly and engaging writing style helps students better understand and retain key concepts A reorganized chapter order provides a more clear and accessible presentation of course material New boxed features highlight new and exciting research in the field Access to the Navigate Companion Website is included with every new print copy Instructor$1 (Bs resources include PowerPoint Lecture Outlines, Power Point Image Bank, Supplementary Problems and Exercises, and a new Test Bank with more than 700 questions. Suitable for a first undergraduate class in evolution, for a class on how organismal diversity arose and is maintained, for an introductory biology class using evolution as the guiding principle, or for a senior undergraduate class that seeks to synthesize a program of study using evolution as the framework.s
Include bibliographical references.; Glossary 579-620p.; Index 621-644p.
Keywords: Biological evolution; Evolutionary biology; Zoology